New protocol for care in the dental health system following the Covid-19 pandemic - Mattos , Belene (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
In 2019 the world experienced a new pandemic and today it continues to leave sequelae on humanity, SARS-CoV-2 became the seventh betacoronavirus to infect the human species, it was characterized by high transmissibility and relatively low lethality; It manifests itself in a mild form in most of the population and increases the probability of severity and lethality in adults over 65 years of age, with previous chronic non-communicable diseases, such as diabetes, arterial hypertension, respiratory diseases and obesity. Knowledge about this virus was built as we went through it, so medicine and all its specialties had to make important adaptations in the forms of patient care. Dentistry in particular, due to having a high exposure to contagion, is in constant review of its care protocols and biosafety standards that are essential for a safe practice for both the professional and the patients. This research, with a cross-sectional descriptive approach, was carried out through the application of an anonymous survey, in order to determine the level of knowledge of the new biosafety protocols from the pandemic, it was applied to 52 practicing dentistry professionals. and a comparison was made with respect to the practices carried out before said pandemic